5-Aminotetrazoles – An Overview of Synthetic Methodologies through the Desulfurization of Thioureas - Moraes, Adriana M.; da Silva, Tiago Lima; de Mattos, Marcio C.S. (Current Organic Chemistry, 2023)
Tetrazoles are important heterocycles in diverse branches of chemistry. Among the 5-substituted tetrazoles, the 5-amino derivatives are the most important by far as they show high chemical versatility and relevant applications in material chemistry, catalysis, agrochemistry, etc. Particularly in medicinal chemistry, they present a wide range of pharmacological properties. In the present review, we focus on the synthesis of 5- aminotetrazol from the desulfurization processes of thioureas using metal salts, hypervalent iodine compounds and halogenated reagents.
Keywords: azidation